Better safe than sorry : the ironies of living with the bomb - Krepon, Michael, 1946- (Stanford Security Studies, 2009)
The bloated nuclear arsenals of the Cold War years have been greatly reduced, nuclear weapon testing has almost ended, and all but eight countries have pledged not to acquire the Bomb. This book believes that positive trends can continue, even in the face of the twin threats of nuclear terrorism and proliferation that have been exacerbated by the Bush administration's pursuit of a war of choice in Iraq based on false assumptions. It advocates a 'back to basics' approach to reducing nuclear dangers, reversing the Bush administration's denigration of diplomacy, deterrence, containment, and arms control.